Which patients risk segmental kyphosis after short segment thoracolumbar fracture fixation with intermediate screws?. (October 2016) - Formica, Matteo; Cavagnaro, Luca; Basso, Marco; Zanirato, Andrea; Felli, Lamberto; Formica, Carlo; Di Martino, Alberto
Abstract: Introduction: The use of intermediate screws in fractured vertebrae has been proposed to decrease the number of fused levels in thoracolumbar fractures and to enable short fixations. The aim of this study was to evaluate the results of this technique and to establish predictive factors involved in loss of segmental kyphosis correction (LKC). Methods: Forty-three patients who underwent short-segment spinal fixation with intermediate screws for a thoracolumbar spine fracture in a two-year time period were enrolled in the study. Patients had AO-type A3, A4 and B2 thoracolumbar fractures. Radiological parameters included segmental kyphosis (SK), vertebral wedge angle (VWA) and loss of anterior and posterior vertebral body height. Patients were evaluated up to one-year follow-up. The correlation between LKC and potential risk factors, such as smoking habit, sex, age, neurological status and BMI was evaluated. Results: Mean preoperative SK was 16.5° ± 6.5°, and it decreased to 3.4° ± 3.5° postoperatively (P < 0.01). At the one-year follow-up mean SK dropped to 5.5° ± 3.9° (P < 0.01). Mean preoperative VWA was 20.0° ± 8.1°, and significantly improved to 6.3° ± 3.1° after surgery (P < 0.01). There was a mean LKC of 1.8° ± 2.1°at one year. LKC mildly correlated with body mass index (BMI, r: +0.31), and obese patients (BMI > 30) had an increased risk of LKC at the one-year follow-up (P = 0.03; odds ratio [OR] = 3.2). Discussion: Analysis of the radiological data at one-year follow-up showed that all the evaluated parameters were associated with a mild loss of correction, with no impact on the clinical outcomes or implant failure. These findings confirm the trends reported in the literature. The correlation between LKC and clinical features, such as BMI, age, sex, smoking habit and preoperative neurological status was investigated. Interestingly, a positive correlation was observed between BMI and LKC, and obese patients with BMI > 30 had an increased risk of LKC at one-year follow-up (OR 3.2); to our knowledge this finding has never before been reported. Conclusion: Short-segment fixation with intermediate screws is a viable technique with positive clinical and radiological outcomes at one-year follow-up. However, surgeons should be aware that in obese patients (BMI > 30) this technique is associated with an increased risk of LKC. Level of evidence: 3.